Sleep disturbance in Sanfilippo syndrome: a parental questionnaire study. Issue 12 (21st November 2005) - Fraser, J; Gason, A A; Wraith, J E; Delatycki, M B
Abstract : Aims: To determine the incidence, manifestations, and best management of sleep disturbance in Sanfilippo syndrome (mucopolysaccharidosis (MPS) type III). Methods: Families were ascertained through the MPS societies of Australasia, the UK, and the USA. Questionnaires were sent by mail and were answered anonymously. Identical questions regarding sleep disturbance were asked about unaffected siblings to provide control data. Sleep disturbance was quantified by a total sleep disturbance score. Results: A total of 141 responses were received; 91.5% of children with Sanfilippo syndrome had sleep disturbance and this was significantly higher than for their unaffected sibs; 77.5% of parents had used medication for this problem, with melatonin and antihistamines being most commonly used. Melatonin and benzodiazepines were reported as the most efficacious. Many different environmental modifications had been employed for this problem and some parents reported success with behavioural therapies. Conclusions: Sleep disturbance is common, severe, and difficult to manage in Sanfilippo syndrome. Based on the parental responses and its safety profile, melatonin is the first line drug that should be tried. Behavioural therapy should be tried in all with Sanfilippo syndrome and sleep disturbance.